Fertigating lettuce (Lactuca sativa L..) using compost teaTT - Fertigation de la laitue (Lactuca sativa L ..) en utilisant le thé de compost - Eudoxie, Gaius (Université des Antilles. Service commun de la documentation (2015-....), 2016)
Crop nutrient management is an essential component of productivity and quality. Commercial horticulture relies almost exclusively on inorganic nutrient sources to meet the nutritional needs of plants. Compost tea is a sustainable alternative technology, but its use has not been thoroughly researched. A factor experiment was conducted by subjecting lettuce plants to four increasing concentrations of compost tea. The concentration of compost tea significantly affected all growth indices showing a similar pattern. Compost tea used at appropriate concentrations improved root growth and lettuce productivity.